FAKTOR RISIKO PENINGKATAN AMBANG DENGAR PEKERJA PENGELASAN (STUDI OBSERVASIONAL PADA PT. X KOTA SEMARANG BERDASARKAN UMUR DAN RIWAYAT PENYAKIT) - Wina Adelia Christi; Ari Suwondo; Baju Widjasena (Jurnal Kesehatan Masyarakat (Undip), 2017)
PT. X is one of the companies engaged in the construction and renovation of buildings that have high noise. Welding workers at PT. X has the risk of exposure to noise from machines cutting and welding metal. The research objective was to analyze the risk factors for the increase in the hearing threshold welding workers at PT. X Semarang based on the age and history of the disease. This study was an observational study with cross sectional analytic. Welding in the working population PT. X as many as 50 people with a sample of 33 people obtained using purposive sampling with inclusion criteria, age 35-70 years old, had no history of hearing, and willing to become respondents. The independent variable in this study is the hearing threshold, while the dependent variable is the age, working life, history of hypertension, history of diabetes mellitus. Methods of data collection using equipment Sound Level Meter to measure noise, Audiometer to measure the hearing threshold, Sphygmanometer to measure blood pressure, Nesco Multicheck to measure blood glucose, and questionnaires. Results of univariate analysis obtained the highest worker age ≤ 40 years (60.6%), working life > 10 years (87.9%), history of hypertension (24.2%), history of diabetes mellitus (21.2%). Bivariate analysis results obtained age (p = 0.435, OR = 0.571), age (p = 0.607, OR = 0.357), and diabetes mellitus (p = 0.203, OR = 4.000) is not a risk factor for the increase in the hearing threshold. While a history of hypertension (p = 0.012, OR = 14.875) is a risk factor for the increase in the hearing threshold. Workers need to maintain health and healthy lifestyle for patients with hypertension that do not have a hearing loss is more severe. In addition, the company is also required to provide a form of earmuff PPE for workers due to occupational noise range 110dB